Utilizing post-stack seismic inversion for delineation of gas-bearing sand in a pleistocene reservoir, baltim gas field, nile delta, Egypt - Ali S. EL-SAYED; Walid M. MABROUK; Ahmed M. METWALLY (Scientific Reports)
Abstract Given useful rock properties, gas sands generally appear as bright events on seismic data. Unfortunately, partially saturated gas sands tend to be of similar brightness to fully saturated gas sands so cannot be distinguished easily. Seismic inversion can sometimes help, given adequate seismic data and a robust understanding of rock physics. This study employs both post- and pre-stack seismic inversion techniques to estimate gas in place (OGIP) and evaluate reservoir properties within the Pleistocene gas sandstone reservoir of the Baltim Field, focusing specifically on the Kanaria prospect. The primary objectives are to estimate gas volumes, assess reservoir properties, and identify optimal well locations. Post-stack inversion is used to detect changes in acoustic impedance, which is essential for hydrocarbon identification, while pre-stack inversion provides insights into rock properties such as density. This approach helps to differentiate true gas sands from other geological features, like water layers or lithological anomalies, which can be misinterpreted as gas zones due to similar seismic responses or fluid variations. Although seismic indicators such as root mean square (RMS) amplitude and AVO analysis can suggest potential gas zones, they may also be affected by similar lithological effects, complicating accurate interpretation. The study confirms the presence of gas-bearing sands in the El Wastani and estimates an OGIP of approximately 0.4 Gm³ for well WB-1 and 6.6 Gm³ for well TERSA-1 ST. By providing detailed reservoir characterization and improving gas estimation accuracy, the findings support informed decision-making for drilling locations and enhance the potential for successful gas production in the Baltim Field.